Europium-based infinite coordination polymer nanospheres as an effective fluorescence probe for phosphate sensing. Issue 14 (27th January 2017) - Song, Xiangyang; Ma, Yue; Ge, Xiao; Zhou, Hongjian; Wang, Guozhong; Zhang, Haimin; Tang, Xiaoxian; Zhang, Yunxia
Abstract : Uniform europium-based infinite coordination polymer nanospheres have been successfully fabricated as an effective fluorescence probe for phosphate sensing. Abstract : Although phosphate plays important roles in aquatic ecosystems as an indispensible nutrient, excessive levels are responsible for severe environmental issues. Hence, it is of considerable significance to develop highly sensitive and reliable probes for the detection of phosphate with the purpose of monitoring of water quality security and early-warning of eutrophication occurrence. In this work, uniform europium-based infinite coordination polymer (Eu-ICP) nanospheres are rationally constructed by a facile one-step solvothermal treatment. It is demonstrated that the newly developed sensing platform features excellent fluorescence properties, which can be efficiently quenched by the presence of phosphate ions (Pi). Typically, a good linearity exists between the decrease in fluorescence intensities and the Pi analyte content ranging from 2–100 μM, allowing the reliable determination of Pi concentration. Accordingly, the detection limit is estimated to be 0.83 μM, which is far below the detection requirement of phosphate discharge criteria in the water environment. It is noteworthy that the prepared Eu-ICP probe displays a specific recognition towards Pi, and is hardly affected by other possible existing species in natural water. More importantly, the proposed fluorescent probe can be utilized for reliable determination of Pi concentration in real water with acceptable recoveries, highlighting its feasibility in complicated environmental samples. Further research suggests that the underlying sensing mechanism is based on the strong affinity between europium centers and Pi, resulting in the collapse of the inherent structure of Eu-ICP and the corresponding fluorescence quenching. These findings show that the developed Eu-ICP probe holds great prospect in monitoring water quality and early warning of eutrophication based on the unique features associated with this simple preparation procedure, high selectivity, and excellent sensitivity.